Hepatitis C Virus Isolates from Argentina Disclose a Novel Genotype 1-Associated Restriction Pattern - Gismondi, María Inés (American Society for Microbiology, 2004)
Hepatitis C virus isolates which disclosed a novel genotype 1-associated restriction pattern by restriction fragment length polymorphism analysis were characterized. Except for a mother and child pair, the patients were unrelated. Sequence analysis showed a G→A substitution leading to a new RsaI recognition site. Phylogenetic analysis revealed that these isolates constitute a novel genetic lineage within the main cluster of genotype 1 strains.